Use of basic programming tools to foster programming logic in university students with school preparation other than computer science - Ibarra-Torres, Fernando; Caiza, Gustavo; García, Marcelo V.; Barona-Pico, Valeria (Procedia computer science, 2024)
Teaching programming logic to students who do not have a background in computer science is challenging, as the instructor has to awaken problem-solving, critical thinking, and logical reasoning skills Several programming tools have been created to teach coding concepts to computer science students of different ages. However, these tools are not well designed to meet the challenge of teaching programming to new developers who come with school training in other areas such as accounting, management, etc. Therefore, this research focused on analyzing the importance of the application of online programming tools to students starting college who come with a school background in an area other than technology. A pre/post experimental design was carried out with 82 first-level students of the Technical University of Ambato in the careers of Systems and Electronics. The results revealed that 45% of the students increased their levels of application and analysis in programming processes. In addition, the research revealed that students who come from a background other than computer science agree with the integration of online programming tools from the first level of university entrance since this method helps to improve their learning capacity.